2014
DOI: 10.1016/j.jelechem.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Rapid optimization of a lactate biosensor design using soft probes scanning electrochemical microscopy

Abstract: a b s t r a c tWe report the mapping of biocatalytically active surfaces, particularly on an express search for optimal immobilization conditions of the enzyme lactate oxidase by means of scanning electrochemical microscopy (SECM). With this aim, soft stylus SECM probes containing a carbon paste ultramicroelectrode were modified with Prussian Blue yielding reproducible hydrogen peroxide (H 2 O 2 ) sensors with a sensitivity of 1.6 ± 0.5 A M À1 cm À2 for screening applications. The ultramicroelectrode response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…[71] Surface coverage can also be deduced from STM images, as was done for Achromobacter xylosoxidans nitrite reductase (Ax NiR) [72] or Escherichia coli cytochrome c nitrite reductase (Ec cyt.c NiR). [73] In situ STM image of Ec cyt.c NiR immobilized on Au (111) showed that the density of enzymes was below the monolayer coverage: 0.5 � 0.1 pmol cm À 2 , which agreed with the fact that it could not be detected in cyclic voltammetry. This coverage estimation enabled further calculation of kinetic constants.…”
Section: Characterization Of the Enzyme Coveragementioning
confidence: 67%
See 3 more Smart Citations
“…[71] Surface coverage can also be deduced from STM images, as was done for Achromobacter xylosoxidans nitrite reductase (Ax NiR) [72] or Escherichia coli cytochrome c nitrite reductase (Ec cyt.c NiR). [73] In situ STM image of Ec cyt.c NiR immobilized on Au (111) showed that the density of enzymes was below the monolayer coverage: 0.5 � 0.1 pmol cm À 2 , which agreed with the fact that it could not be detected in cyclic voltammetry. This coverage estimation enabled further calculation of kinetic constants.…”
Section: Characterization Of the Enzyme Coveragementioning
confidence: 67%
“…To avoid topographic artifacts, imaging was moreover performed in contact mode with a soft probe. Soft microelectrodes indeed enable contact scanning at constant distance, without risk of damaging the sample or the tip . More recently, the detection of local hydrogen evolution by a hybrid biocatalyst based on PSI and platinum nanoparticles immobilized in a redox polymer on a gold electrode has been performed by scanning photo‐electrochemical microscopy using a hydrogenase‐modified microelectrode.…”
Section: Imaging Of Local Redox Activity/mapping Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…The principle has been demonstrated first for a soft carbon microelectrode probe (the so-called Soft Stylus Probe) to scan rough and tilted substrates without obtaining topographic artifacts. [1,2] Initially, the probe fabrication was carried out by UV laser ablation on a thin polyethylene terephthalate film to form a microchannel that was filled subsequently with a conductive carbon paste and sealed with an insulating covering layer. Later, other microfabrication techniques such as aerosol jet printing, [3] inkjet printing, Parylene coating of Pt wires [4] and sealing Pt wires in glass sheaths [5] have increased the versatility of the newly designed probes and applications for soft SECM contact mode imaging.…”
Section: Scanning Electrochemical Microscopymentioning
confidence: 99%